Dynamics of dyke intrusion in the mid-crust of Iceland - White, R. S.; Drew, J.; Martens, H. R.; Key, A. J.; Soosalu, H.; Jakobsdottir, S. S. (Earth and Planetary Science Letters, 2011)
We have captured a remarkable sequence of microearthquakes showing progressive melt intrusion of a dyke moving upward from a sill at 18 km depth in the mid-crust of the northern volcanic rift zone in Iceland. Two-thirds of the earth's crust is created at mid-ocean rifts. Two-thirds of that crust is formed by intrusion and freezing before it erupts of molten rock generated within the underlying mantle. Here we show seismicity accompanying melt intrusion from 17.5 to 13.5 km depth along a dyke dipping at 50° in the mid-crust of the Icelandic rift zone. Although the crust at these depths is normally aseismic, high strain rates as melt intrudes generate microearthquakes up to magnitude 2.2. Moment tensor solutions show dominantly double-couple failure, with fault mechanisms sometimes flipping between normal and reverse faulting within minutes in the same location, but breaking along fault planes with the same orientations. We suggest several possible reasons for the flipping fault mechanisms: the breakage of solidified plugs of basalt within the dyke itself as more melt intrudes; intrusion along sub-parallel fractures or dykelet fingers into the local stress field created near the tip of a propagating dyke; or movement on small jogs or offsets between adjacent en echelon dykes. Although the faulting is caused ultimately by melt movement, there is no resolvable volumetric component in the moment tensor solutions. The inferred fault planes from microearthquakes align precisely with the overall plane of the dyke delineated by hypocentres. Melt injection occurs in bursts propagating at 2–3 m/min along channels c. 0.2 m thick, producing swarms of microearthquakes lasting several hours. Intervening quiescent periods last tens to hundreds of hours.